Existing barriers in research and rehabilitation - Putra Jaya, Ramadhansyah; Norhidayah, Abdul Hassan; Munirwan, Reza Pahlevi (Popular Scientist Publisher, 2025)
We are thrilled to introduce the 2025 edition of the Current Problems in Research Journal. This first volume highlights the ongoing challenges in research and rehabilitation. Rehabilitation challenges extend beyond reconstruction, emphasizing improvement to build greater resilience for future research issues.